Mullahs, guards, and bonyads : an exploration of Iranian leadership dynamics - Thaler, David E. (Rand Corporation monograph series., 2010)
The Islamic Republic of Iran poses serious challenges to U.S. interests in the Middle East, and its nuclear program continues to worry, and bring condemnation and sanction from, the international community. Yet the U.S. ability to "read" the regime in Tehran and formulate appropriate policies has been handicapped by the lack of access to Iran experienced by U.S. diplomats and other citizens and by what many observers lament as the opacity of Iranian decisionmaking processes. The objective of this book is to offer a framework to help U.S. policymakers and analysts better understand existing and evolving leadership dynamics driving Iranian decisionmaking. The research herein provides not only a basic primer on the structure, institutions, and personalities of the government and other influential power centers but also a better understanding of Iranian elite behavior as a driver of Iranian policy formulation and execution. The book pays special attention to emerging fissures within the regime, competing centers of power, and the primacy of informal networks-- a particularly important yet not well understood hallmark of the Iranian system